Palladium supported graphene oxide based metal organic framework composite for hydrogen technology - Makhafola, Mogwasha Daphney (My University, 2019)
The concept of sustainable energy development is one of the crucial topics of the 21st century. It has evolved into a guiding principle for a liveable future world where human needs are met while maintaining balance with the environment. In this regard, hydrogen technology is a promising alternative energy source since it does not produce undesirable greenhouse gas (CO2). In order to place hydrogen energy into practical applications, there are certain problems that need to be addressed, these include the efficient production and storage of hydrogen. Currently, hydrogen is mostly produced from conventional processes such as steam reforming of fossil fuels, gasification and water splitting (photo/electrochemical and thermochemical). Among these methods, electrochemical water splitting is identified as a noble process to produce clean hydrogen gas and monitor all processes through hydrogen evolution reactions (HER). The entire HER processes are sluggish in nature and cathodic electrocatalysts are utilised to accelerate the process. Hence, in this work, we present highly active graphene oxide/metal organic framework (GO/MOF) and palladium (Pd) supported GO/MOF electrocatalysts for HER. GO/MOF was prepared through impregnation method of MOF and GO, whereas Pd@GO/MOF composite was synthesised using electroless Pd deposition on GO and followed by impregnation method of direct mixing of Pd@GO and MOF. The structural, morphological and electrochemical properties of the synthesised materials (GO/MOF and Pd@GO/MOF) were characterised by X-ray diffraction (XRD), Fourier transform infrared (FTIR), simultaneous thermogravimetric analysis (STA), scanning electron microscopy/energy dispersive spectroscopy (SEM/EDS), high resolution transmission electron microscopy/Energy dispersive x-ray spectroscopy/selected area electron diffraction (HRTEM/EDX/SAED) and cyclic voltammetry (CV). XRD, FTIR, TGA and DSC results revealed the presence of GO on MOF confirming the formation of composites. The SEM/EDS and HRTEM/EDX/SAED results confirmed the presence of octahedral structure of MOF in the Pd@GO sheet-like structure, elemental composition and crystallinity of the synthesised materials. Furthermore, the electrocatalytic efficiency of GO/MOF and Pd@GO/MOF composites on HER was studied using three important parameters (exchange current density, Tafel slope and charge transfer coefficient) calculated from Tafel analysis. The GO/MOF and Pd@GO/MOF composites showed excellent HER activity at 0.45 mol.L-1 H2SO4 withexchange current densities of 25.12 A.m-2 and 24.5 A.m-2, Tafel slopes of 116 mV/dec and 123 mV/dec, and transfer coefficients of 0.49 and 0.52, respectively. These observed results are consistent with theory, thus suggesting the Volmer reaction as the limiting mechanism at high concentration. However, at low concentration both composites showed an increase in the Tafel slope and transfer coefficient, suggesting the reaction order of Volmer reaction coupled with either Heyrovsky or Tafel reaction. The proposed reaction order was further supported by slope of logarithm of current as a function of pH and Pourbaix diagram. The composites demonstrated the enhancement turnover frequency (TOF) values in this order MOF <GO/MOF <Pd@GO/MOF. The large TOF value of 7.81 mol H2.s-1 in the case of Pd@GO/MOF was due the H2 spillover effect as a result of the presence of Pd nanoparticles. The fabricated composites displayed high activity, good stability and excellent tolerance to the crossover effect, which may be used as a promising catalyst in electrochemical hydrogen production and storage technology via hydrogen evolution reaction.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2019.
Keywords: Palladium; Graphene oxide; Hydrogen technology; Palladium - Isotopes; Energy development